Concentration and time-dependent amyloidogenic characteristics of intrinsically disordered N-terminal region of Saccharomyces cerevisiae Stm1 - Subbaiah S P, Venkata; Uttamrao, Patil Pranita; Das, Uttam; Sundaresan, Sruthi; Rathinavelan, Thenmalarchelvi (Frontiers in Microbiology, 2023)
Saccharomyces cerevisiae Stm1 protein is a ribosomal association factor which plays an important role in preserving ribosomes in a nutrition-deprived environment. It is also shown to take part in apoptosis-like cell death. Stm1 N-terminal region (Stm1_N 1-113 ) is shown to recognize purine motif DNA triplex and G-quadruplex. Circular dichroism (CD) spectra of Stm1_N 1-113 (enriched in positively-charged Lysine and Arginine, negatively-charged Aspartate, polar-uncharged Threonine, Asparagine, Proline and Serine; hydrophobic Alanine, Valine and Glycine) collected after 0 hr and 24 hrs indicate that the protein assumes beta-sheet conformation at the higher concentration in contrast to intrinsically disordered conformation seen for its monomeric form found in the crystal structure. Thioflavin-T kinetics experiments indicate that the lag phase is influenced by the salt concentration. Stm1_N 1-113 AFM images collected for a variety of concentrations (in the range of 1 µM to 400 µM) in the presence of 150 mM NaCl at 0 hr, 24 hrs, and 48 hrs indicate a threshold concentration requirement to observe the time-dependent amyloid formation. This is prominently seen at the physiological salt concentration of 150 mM NaCl with the fibrillation at 400 µM concentration after 48 hrs, wherein oligomerization or proto-fibrillation is seen at the other concentrations. Such concentration-dependent fibrillation of Stm1_N 1- 113 explains that amyloid fibrils formed during the overexpression of Stm1_N 1-113 may act as a molecular device to trigger apoptosis-like cell death.